Reassessing Trade Unions’ Role in Achieving Fair Industrial Relations - Panji Purnomo Adhi; Naning Indriyawati; Basuki Tri Setiawan; Dara Puspitasari (JUSTISI, 2026)
This study aims to analyze the role of labor unions in achieving industrial relations justice in Indonesia and to identify whether the legal issues that arise stem from weaknesses in the norms or from the effectiveness of implementing the norms of freedom of association. This study uses a normative-conceptual legal method by examining constitutional provisions, labor laws and regulations, ILO conventions, as well as industrial relations theory and theories of justice. Data were obtained through a literature review encompassing primary, secondary, and tertiary legal sources, and were then qualitatively analyzed to assess the effectiveness of trade unions’ role within the national labor law system. The novelty of this research lies in the assertion that the primary issue in achieving industrial relations justice does not stem from a lack of legal norms, but rather from the gap between the normative guarantees of freedom of association and their implementation in industrial relations practice. The results of the study indicate that, normatively, the legal framework regarding freedom of association and the role of labor unions is adequate. Trade unions serve as providers of legal protection, balancers of bargaining power in collective bargaining, and facilitators of tripartite social dialogue. However, the effectiveness of these roles still faces obstacles in the form of limited institutional capacity, organizational fragmentation, increasing flexibility in employment relationships, and suboptimal law enforcement. The conclusion of this study is that efforts to improve industrial relations justice must be directed toward strengthening the effectiveness of the implementation of freedom of association norms through institutional strengthening of labor unions, consistent labor oversight, and the state’s commitment to ensuring substantive protection of the right to organize.